On the economic impact of droughts in central Europe: the decade from 1531 to 1540 from the Polish perspective - Związek, Tomasz; Guzowski, Piotr; Poniat, Radosław; Radomski, Maciej; Kozłowska-Szyc, Monika; Panecki, Tomasz; Słowińska, Sandra; Kruczkowska, Bogusława; Targowski, Michał; Adamska, Dagmara (Copernicus Publication, 2022)
The period from around 1450 to 1550 in Europe is extremely interesting from the perspective of research on extreme weather events. It was a period of events that strongly influenced the societies and economies of the Old Continent.So far, the literature has been more focused on western and northern Europe. Concerning the region of central Europe,the greatest attention was paid to the Czech Republic or Hungary. This article revolves around the Polish lands, which experienced their greatest economic boom in the 16th century.We consider whether and how the droughts of the decade from 1531 to 1540 might have affected the country’s economic development. We analyse a number of written sources which are the product of the treasury apparatus of the time (tax registers, data from water customs, tax exemptions, inventories of land estates etc.), but also information on fluctuations in product prices in the most important cities in this part of Europe. The work not only provides a detailed account of economic data, but also attempts to reflect on the relevance of linking information on fires in urban centres in the period characterized by weather extremes.